AB0124 Serological measures of b cell function in patients with sle; how robust are they over time?. (15th June 2017) - Hennessey, A; Marques, R; Leandro, M; Isenberg, D; Cambridge, G
Abstract : Background: In SLE the precise mechanisms whereby parent autoreactive B cells are generated and permitted to escape tolerance checkpoints, proliferate, persist and switch to pathogenic autoantibody production remains poorly understood. Hypotheses include defective negative central selection, defective peripheral selection with enhanced germinal center activity as well as positive selection of B cells via autoantigen presentation or T-independent mechanisms. Biomarkers to identify possible breaches in tolerance checkpoints would allow more effective intervention. We have therefore measured relative levels of soluble (s)CD23 (released during B cell differentiation from naive to memory B cell status) and the B cell activation factor, BAFF (survival factor and class-switch/differentiation promoter) in SLE sera to determine if relative levels of sCD23 and BAFF were of use as biomarkers to group patients based on B cell kinetics rather than clinical features. BAFF is often raised in SLE patients and can stimulate the aberrant differentiation of transitional B cells and of plasmablasts in vitro. Combining the 2 biomarkers could therefore indicate whether there was increased expansion of naïve B cells, and whether BAFF was a possible driver/consequence of autoimmunity in different patients. Objectives: To determine whether relative levels of sCD23 and BAFF reflect disease activity or remain stable over time. Methods: Stored SLE serum from patients who were Rituximab-naive, had >5 samples available in the biobank over at least 6 months (n=38). Samples were analysed for levels of sCD23 and BAFF via ELISA. Wilcoxon matched-pairs signed rank test were used to compare serial values. Clinical details including BILAG scores were also collected for the available time points. If positive dsDNA at any time during the time period this was deemed positive. The latest BILAG was utilised and reviewed, a patient was deemed not to have system involvement if they had an "E" for that system. Results: Sera from 38 SLE patients (32 female, 6 male) with mean age of first sample 42 (range: 25–72). Minimum interval between 1st and last sample was 101 weeks (range: 35–192 weeks). Patients were then sorted into clinical groups according to levels of these serum markers. Normal ranges defined as: sCD23 (1235–5023pg/ml), BAFF (584–1186pg/ml). Group I (n=9): – High (H) sCD23, Normal (N) BAFF; Group II (n=11) – H sCD23, H BAFF; Group III (n=17) – N sCD23, N BAFF; Group IV (n=2) – N sCD23, H BAFF. Figure 1 shows the p values generated from the Wilcoxon matched-pairs signed rank test for each time period demonstrating nil significant change over time. Analysis of clinical data showed no differences in terms of organ involvement or anti-dsDNA -Ab status. Conclusions: Within a cohort of SLE patients, soluble CD23 and BAFF is stable over time despite variation in disease activity. Grouping patients based on sCD23 and BAFF profile may be useful in identifying distinct B cell maturation pathways reflecting underlying autoimmune pathways which vary between patients. Disclosure of Interest: A. Hennessey: None declared, R. Marques: None declared, M. Leandro Consultant for: Roche UK, Roche Basel and Genentech, D. Isenberg: None declared, G. Cambridge: None declared